Proceedings of the 5th Information Interaction in Context Symposium 2014
DOI: 10.1145/2637002.2637010
|View full text |Cite
|
Sign up to set email alerts
|

A user defined taxonomy of factors that divide online information retrieval sessions

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. ABSTRACTAlthough research is increasingly interested in session-based retrieval, comparably little work has focused on how best to divide web histories into sessions. Most automated att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Research has found that multi-tasking is quite common in Web search (Ye & Wilson, 2014). For example, Spink, Ozmutlu, and Ozmutlu (2002) found that 11.4% of 1,000 randomly extracted sessions involved multitasking.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that multi-tasking is quite common in Web search (Ye & Wilson, 2014). For example, Spink, Ozmutlu, and Ozmutlu (2002) found that 11.4% of 1,000 randomly extracted sessions involved multitasking.…”
Section: Introductionmentioning
confidence: 99%